Factors Affecting the Impact of Child Advocacy Offices in Canada - Howe, R. Brian (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2009)
International interest in children's rights and in official child dvocacy agencies responsiblefor pomoting the rights and voices of children is increasing. This article examines theconventional wisdom on factors that enhance the impact of these agencies. It does sothrough a stucly on the impact of provincial child dvocacy offices in Canada. In linewith conventional wisdom, the findings show that, in general, a higher level of impactis associated with offices that are independent from government, exclusively focused onchildren, accessible to children, and that have a wide marulute, strong statutory powers,and a broad advocacy function. But what also is suggested in the findings is the importanceof a factor not given attention in the conventional wisdom - slcillful ledership in thecontext of a receptive political culture. In conjzinction with or in the absence of othe~facilitating factors, leadership in a supportive political environment can play a significantrole in acluancing the rights of children.On assiste dans le monde entier h un regain d'inte'rzt pour les h i t s des enfants et lesorganismes de &fense de l'enfance qui sont responsables de la promotion des droits etde la voix des enfants. Duns cet article, on examine les ide'es resues sur les facteurs quirehaussent l'influence de ces organismes et, notamment, par une e'tucle sur l'influence desorganismes provinciaux de de'fense de l'enfance au C a d . A l'instar des ide'es repes,l'e'tude conclut qu'un niveau plus ileue' d'injluence est observe' dans les organismes qui sontindipendants des pouvoirs publics, exclusivement axes sur les enfants, accessibles aux enfants, et cew qui ont un waste mandat, lles robustes pouwoirs statutuires et une amplefonction de repr6sentation. Cependant, les re'sultuts montrent aussi l'importunce d'unfacteur qui n'a pas suscite' lJmt6rZt des wues traditionnelles : le leadership awist! dansle contexte d'une culture politique re'ceptiwe. Une lles conclusions tire'es weut qw conjointernentawec, ou en l'absence, d'autres fucteurs facilitateurs, le ledership peut jouer unr8le iml~ortandt ans la promotion des droits lles enfants.